Kajian Kewirausahaan dengan Kinerja Pemasaran serta Desain Strategi Pemasaran Depot Air Minum Isi Ulang Gunung Salju - Cahyani, Eni; Masdaini, Efrina; Septiani, Dian (Universitas muhammadiyah palembang, 2020)
This research was conducted at the Refill drinking water Depot, an effort of micro small and medium businesses to determine the entrepreneurial relationship with Marketing Performance so that UMKM can take steps to improve marketing through designing marketing strategies. The technique used in writing this research is interview, observation and documentation in the form of writings, drawings or monumentel works from someone. To test the validity of the data obtained so that it is truly in accordance with the aims and objectives of the study, the researchers used triangulation techniques. The data analysis technique used in this study refers to the interactive model. The results of the study conclude there is a link between entrepreneurship and marketing where entrepreneurial behavior can be said as behavior that represents more informal and unplanned activities that rely on intuition and energy from individuals to realize business activities in determining marketing strategies. Then the marketing strategy designs compose namely relying on product excellence, expanding market networks, establishing cooperation, promoting door to door, cost efficiency and increasing external capital.